Polymerase chain reaction-based open reading frame typing (POT) method analysis for a methicillin-resistant Staphylococcus aureus (MRSA) outbreak through breast-feeding in the neonatal intensive care unit. (2018) - Kato, Hideaki; Ide, Kazuo; Fukase, Fumie; Shimura, Yukihiro; Yasuda, Shuhei; Goto, Hideto; Fukuyama, Ayako; Nakajima, Hideaki
Abstract: Introduction: The route of methicillin-resistant Staphylococcus aureus (MRSA) transmission in the neonatal intensive care unit (NICU) is not clearly explained. We investigate an MRSA outbreak involving five babies in the NICU. The molecular investigation using polymerase chain reaction-based open reading frame typing (POT) method was performed. Presentation of outbreak: A MRSA outbreak occurred in a six-bed NICU affecting 5 babies. Within 13 days of the emergence of index case, all five babies including triplets and other two babies were found to colonize MRSA by the active surveillance culture. Environmental surveillance cultures revealed that the preserved breast milk provided by the triplets' mother was the only item in the NICU that was positive for MRSA. The mother had a bite wound on the nipples, and the breast milk was not pasteurized. The POT method revealed that MRSA strains detected from the triplets, the breast milk, and the other baby who was fed the triplets' mother's milk were genetically identical (POT index: 106-247-33). The all strains of MRSA carried Staphylococcal cassette chromosome mec (SCC mec ) IV and had good susceptibility for the non-ß-lactam antimicrobial agents, suggesting the strains were community-acquired MRSA. Conclusions: The mother's milk contaminated with community-origin MRSA is serving as the reservoir of MRSA and one of the sources of MRSA outbreaks in the NICU. It is important to closely monitor the condition of the mothers of the children in the NICU. Pasteurization of breast milk should be considered when the skin on the nipple is broken.